2002
DOI: 10.1001/archpedi.156.10.1042
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary Therapy by Adolescents With Asthma

Abstract: Most adolescents with asthma in this study used CAM. The prevalence of CAM use in this study population was twice the national average for adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
73
2
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 16 publications
8
73
2
3
Order By: Relevance
“…Most the young adult participants 69.1% showed that use unconventional medicine in their life. Similar to previous studies [12,13] indicted that 71% and 80% of young adult using UM. In our study indicated that Quran/Roqua/pray, herbal medicine, honey therapy and sports therapy are common type of UM used by the young adults which similar to previous study include young adults and adults in Qassim Province [10] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most the young adult participants 69.1% showed that use unconventional medicine in their life. Similar to previous studies [12,13] indicted that 71% and 80% of young adult using UM. In our study indicated that Quran/Roqua/pray, herbal medicine, honey therapy and sports therapy are common type of UM used by the young adults which similar to previous study include young adults and adults in Qassim Province [10] .…”
Section: Discussionsupporting
confidence: 88%
“…This study similar to previous studies that young adults can be affected by people [10,19] . The most common reason of using UM is treating illness which similar to other studies [10,12,13,19] . In this study showed similar previous studies [20] the young adult showed positive attitude about UM.…”
Section: Discussionmentioning
confidence: 54%
“…Prior research on CAM use in asthma showed fairly high prevalence rates of CAM use among children (Braganza, Ozuah, & Sharif, 2003;Crawford, Cincotta, Lim, & Powell, 2006;Mazur, DeYbarrondo, Miller, & Colasurdo, 2001;Reznik, Ozuah, Franco, Cohen, & Motlow, 2002;Shenfield, Lim, & Allen, 2002) yet the results of studies on CAM therapies do not generally support their efficacy in treating asthma (Angsten, 2000;Bielory, 2004;Bielory, Russin, & Zuckerman, 2004;Blazek-O'Neill, 2005;Gardnier & Wornham, 2000;Graham & Blaiss, 2000;Gyorik & Brutsche, 2004;Heimall & Bielory, 2004;Markham & Wilkinson, 2004). CAM prevalence rates (lifetime and current) among children with asthma range from 52% to 89% (Braganza et al; Mazur et al; Reznik et al; Shenfield et al).…”
mentioning
confidence: 99%
“…Studies have found as many as 72% to 89% of Hispanics use or are aware of ethnomedical, complementary and alternative medicine (CAM), and home or folk remedies for asthma. [21][22][23][24][25][26][27][28] [26][27][28] and information source 25 on use or perceived effi cacy. In the context of this study, ethnomedical treatments are nonallopathic treatments that are part of a system of healing practices, beliefs, and social relations of an ethnic group, derived mostly from the popular (lay, nonprofessional, nonspecialist) and folk (nonprofessional, specialist) health care sectors.…”
mentioning
confidence: 99%
“…29 A study of CAM use among asthmatic adolescents found that participants were signifi cantly more likely to use CAM again if they had a family member who used CAM and if they perceived CAM to be effective. 25 Another study determined that perceived effi cacy of biomedical and ethnomedical therapies may depend on whether the condition being treated is considered a folk illness. …”
mentioning
confidence: 99%